Density Forecasts Based on Disaggregate Data: Nowcasting Polish Inflation - Mazur, Błażej (Dynamic Econometric Models, 2015)
The paper investigates gains in performance of density forecasts from models using disaggregate data when forecasting aggregate series. The problem is considered within a restricted VAR framework with alternative sets of exclusion restrictions. Empirical analysis of Polish CPI m-o-m inflation rate (using its 14 sub-categories for disaggregate modelling) is presented. Exclusion restrictions are shown to improve density forecasting performance (as evaluated using log-score and CRPS criteria) relatively to aggregate and also disaggregate unrestricted models.